1990
DOI: 10.1159/000200349
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin Release by Gastric Distension – An Atropine-Sensitive Mechanism

Abstract: The effect of gastric distension on plasma cholecystokinin (CCK), pancreatic polypeptide (PP) and gastrin concentrations was investigated in healthy volunteers. Fundic and antral distension was achieved by balloons attached to a gastric tube and inflated with 300 and 600 ml and 100 and 200 ml of air for fundic and antral distension, respectively. Gastric juice was continuously aspirated. Fundic distension was additionally studied during a concomitant intravenous infusion of atropine (5 µg/kg/h) or a bolus inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…This finding is in contrast with data from another study in humans30 in which an 81% increase in plasma CCK was observed after fundic distension. In contrast, antral distension does not appear to cause CCK secretion 30…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is in contrast with data from another study in humans30 in which an 81% increase in plasma CCK was observed after fundic distension. In contrast, antral distension does not appear to cause CCK secretion 30…”
Section: Discussioncontrasting
confidence: 99%
“…This may suggest that, in contrast to PYY and ghrelin, gastric distension, enhanced by the greater amount of food eaten during the FAT-THL condition, may be a more important stimulus for PP. Indeed, moderate gastric distension with a balloon (volume: 600 ml) has been shown to cause a substantial (71%) increase in PP secretion in healthy volunteers (20). Alternatively, it is possible that the other macronutrients, carbohydrate and protein, are more important stimuli for PP secretion than fat.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we perfused the peptone through the stomach, with continuous aspiration of the antrum to avoid any effects of distension on gastrin release. Koop et al [12] have demonstrated that fundic distension in man increases basal gastrin by 31 %. which may explain why our peptone-stimulated gastrin release was rela tively small compared with previous studies of intragastric titration [17,29], In addition to distending the stomach, the method of intragastric titration may also chemically stimulate gastrin cells to a greater extent since the peptone is not perfused through the stomach as it was in our study, but is rela tively static.…”
Section: Discussionmentioning
confidence: 97%
“…To test this, we measured plasma gastrin concentrations during stimula tion of the stomach with 4% peptone solu tions at pH 2.5 and at pH 5.5 before and after suppression of H. pylori. The gastric pH was kept constant by titration with alkali, and the meal was perfused through the stomach by a method that we have previously used to avoid the effects of gastric distension [10][11][12],…”
mentioning
confidence: 99%